(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research discusses one of the most critical issues of corporate finance which is related to asset utilization efficiency. Researchers used internal growth rate as independent variable (Proxy of asset utilization efficiency) and sustainable growth rate-dependent variable (proxy of stockholders wealth). According to these two variables, researchers formulate major hypotheses (There is no significant effect of internal growth rate on sustainable growth rate), as well as two sub-hypotheses, examine the components of major variables. Sample of Iraqi industrial companies which listed in the Iraqi stock exchange selected to test and examine main hypotheses. Result of simple and multiple regressions explain there is a significant effect of internal growth rate on the sustainable growth rate. Other things are fixed; the study concludes that this impact means that the wealth of stockholders will be sustains depend on asset utilization efficiency level. Therefore, although the current conditions of Iraqi economy, the Iraqi companies (research sample) tried to utilize their available asset to keep sustainable owners wealth. The researchers recommended the listed of Iraqi companies in the stock exchange discloser in their financial statements the internal growth rate and sustainable growth rate to help and guide investors while they formulate investment decisions.